Cross-frequency coupling within and between the human thalamus and neocortex - Fitzgerald, Thomas H.; Valentin, Antonio; Selway, Richard; Richardson, Mark P. (Frontiers in Human Neuroscience, 2013)
There is currently growing interest in, and increasing evidence for, cross-frequency interactions between electrical field oscillations in the brains of various organisms. A number of theories have linked such interactions to crucial features of neuronal function and cognition. In mammals, these interactions have mostly been reported in the neocortex and hippocampus, and it remains unexplored whether similar patterns of activity occur in the thalamus, and between the thalamus and neocortex. Here we use data recorded from patients undergoing thalamic deep-brain stimulation for epilepsy to demonstrate the existence and prevalence, across a range of frequencies, of both phase–amplitude (PAC) and amplitude–amplitude coupling (AAC) both within the thalamus and prefrontal cortex (PFC), and between them. These cross-frequency interactions may play an important role in local processing within the thalamus and neocortex, as well as information transfer between them.